PENGARUH KUALITAS PRODUK, KEPERCAYAAN KONSUMEN DAN PROMOSI TERHADAP KEPUASAN KONSUMEN PT. VARIA USAHA BETON DI SIDOARJO - I Made Bagus Dwiarta (Fakultas Ekonomi Universitas PGRI Adi Buana, 2016)
ABSTRACT The company has the task to manage economic resources, or often called the factors of production are: human, material, method, money market and the machine. PT Varia Usaha Beton is a company engaged in Concrete Pre printed and lightweight Concrete. To obtain the necessary data, the authors use the technique of collecting data in the form of a detailed questionnaire, documentation, interviews, and observations taken with the technique of sampling acidental. Observation and data analysis using the method of using quantitative methods. Types of data used in the form of primary and secondary data. Multiple Linear regression analysis of the obtained results the regression coefficient values i.e. statement of product quality, regression coefficient value trust, and the regression coefficient value promotion is positive, meaning if the quality of the product (X1), trust (X2), and promotion (X3) increases, it will increase customer satisfaction and Add (Y). Hypothesis testing using the Test coefficients of determination (R²) Test, f Test and t Test coefficient determination. (R²) shows that consumer satisfaction variables that can be described variable product quality, trustworthiness, and promotions have a very powerful influence, F-test showed that based on the level of their significance, then the inferred Ha accepted and Ho rejected. This means a variable product quality, trustworthiness, and promotions simultaneously had a significant influence toward consumer satisfaction, t test showed that the value of the regression coefficient is positive significance and value to product quality, trustworthiness, and promotion is indicating that product quality, trustworthiness, and promotions have significant influence towards consumer satisfaction. Therefore customer satisfaction will increase if product quality, trust and Promotion in accordance with what is desired by consumers, particularly customers of PT Varia Usaha Beton. Keywords: Product Quality, Trust, Promotion and Costomer Satisfaction.